WOMEN IN THE IDENTITY CRISIS OF FEMINISM; A CRITICAL ANALYSIS ON GENDER MOVEMENT BASED ON ISLAMIC PSYCHOLOGY PERSPECTIVE - Septi Gumiandari; Ilman Nafi'a (HUMANISMA : Journal of Gender Studies, 2019)
This paper attempted to analyze critically the women's movement that had been developing so far and tried to offer the ideology of the gender movement based on the values of humanism of Islamic Psychology. This study used a qualitative methodology with a literature approach. The results showed that (1) the male clone tendency in the women's movement had actually been predicted by various parties, including by the female activists. Because of the obsession to equalize the active role of women as equal to men, the women's movement was trapped in standardizing themselves with male masculinity figures. On one hand, they rejected male domination on women, but on the other hand the ambitions of their movements are directed towards seizing the dominant patriarchal system and violating it under the authority of women. Even though Islam places women in the frame of proportionally optimistic rational roles. That is, Islam does not make women fully pretend to be 'backward' entities so that it does not allow them to gain enlightenment and Islam rejects thoughts that are too optimistic to position 'front' women as the sole determinant of their lives and must be above men. Both of these views have reduced women to fall into the destruction or glorification of human quality by ignoring the greatness and power of Sunnatullah over the surrounding conditions; (2) Acording to the values of humanism of Islamic Psychology, the ideology of the gender movement should depart from the needs and be based on a) Women’s self-actualization rather than self-exploitation; b) Women’s Active participation rather than their mobilization and domestication. (c) Partnership rather than rivalism.